Is kohl dangerous? / Noraziah Mohd Amin - Mohd Amin, Noraziah (Academy of Language Studies, 2021)
The word, “kohl” is derived from the Arabic, “kuhl”, “kuhl”, “kohhel”, “kohol” and “cohol” which means “powder used to darken the eyelids, eyelashes and eyebrows.” Kohl is also known as “surma” which is an Urdu word to refer to antimony, as its major component is antimony sulphide (Goswami, 2013). According to Goswami (2013), surma is a mineral that is mined and ground into a form of powder, and it has been used for centuries for cosmetic purposes and to ward off evil forces. Kohl or surma is also called “kajal” in India and “tiro” in Nigeria (Hardy et. al., 1998).